Conditioning factors for the development of the self-care competence in the person with a tracheostomy - Queirós, Sílvia (2017)
Background: The development of the self-care competence in the person with a stoma promotes a healthy transition to a life with a stoma. Studies suggest the existence of factors conditioning the development of the ostomy self-care competence. Objectives: To identify the conditioning factors for the development of the self-care competence in the person with atracheostomy. Methodology: A quantitative, descriptive, and cross-sectional study was conducted in a nonprobability sample composed of 80 participants. Data were collected using the “Assessment Form of the Self-Care Competence in the Person with a Tracheostomy. Results: The conditioning factors for the development of the tracheostomy self-care competence were: being a man, having low schooling, having had an emergency surgery, having a temporary ostomy, and having a caregiver. The postoperative period proved to be a facilitating factor. Conclusion: The recognition of the existence of factors conditioning the development of the tracheostomy self-care competence allows nurses to identify conditions of vulnerability in their patients and adapt their interventions with a view to enhancing their autonomy.